2004
DOI: 10.1210/jc.2003-031826
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Inflammation, and the Expression of the Metabolic Syndrome in Obese Individuals: The Impact of Rapid Weight Loss through Caloric Restriction

Abstract: Severe obesity increases the prevalence of the metabolic syndrome, and moderate acute weight loss with a very low-calorie diet in obese subjects with the metabolic syndrome leads to significant metabolic benefits. Adiponectin has been implicated in both the pathogenesis of obesity-related insulin resistance and increased inflammation. We analyzed the relationship of the adipocyte-derived hormone adiponectin with indices of inflammation, adiposity, and insulin resistance in obese subjects with (MS+, n = 40) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
169
4
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(210 citation statements)
references
References 52 publications
26
169
4
11
Order By: Relevance
“…25,26 Given that the subjects remained obese after the present study's 12-week weight loss period, it seems likely that a critical amount of total adiposity must be lost before the weight loss effect on this cytokine is observed, so the adipocyte resumes a more balanced function. 27 At this time, the mechanisms regarding the different effects of weight loss shown in MHO and MAO individuals have not been elucidated. Although the MHO individuals' clinical markers did not reflect the beneficial effects of weight loss in the present study, these results should not persuade us to underestimate the positive effects of lifestyle modifications, including weight loss, on MHO individuals.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Given that the subjects remained obese after the present study's 12-week weight loss period, it seems likely that a critical amount of total adiposity must be lost before the weight loss effect on this cytokine is observed, so the adipocyte resumes a more balanced function. 27 At this time, the mechanisms regarding the different effects of weight loss shown in MHO and MAO individuals have not been elucidated. Although the MHO individuals' clinical markers did not reflect the beneficial effects of weight loss in the present study, these results should not persuade us to underestimate the positive effects of lifestyle modifications, including weight loss, on MHO individuals.…”
Section: Discussionmentioning
confidence: 99%
“…26 Circulating adiponectin concentrations are reduced in patients with T2D and are associated with the metabolic syndrome. 9,27 Data from human cross-sectional studies have shown intra-abdominal adipose tissue as an important determinant of plasma adiponectin, implying that adiponectin might link visceral obesity and insulin resistance. Findings of Lihn et al 28 describing lower adiponectin gene expression in visceral adipose tissue support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in rodent models of atherosclerosis, such as ob/ob and apoEdeficient mice, adiponectin reportedly exerts a protective effect on the development of both atherosclerosis and type 2 diabetes mellitus (Frühbeck, 2004a;Lau et al 2005). The findings in animals have a certain clinical parallel in human subjects, evidenced by a negative correlation between adiponectinaemia and markers of inflammation (Pischon et al 2004;Xydakis et al 2004). Circulating adiponectin levels have been observed to be inversely correlated with insulin resistance and C-reactive protein concentrations (Ouchi et al 2003).…”
Section: Adiponectinmentioning
confidence: 99%